1977
DOI: 10.1039/c39770000164
|View full text |Cite
|
Sign up to set email alerts
|

Cathenamine, a central intermediate in the cell free biosynthesis of ajmalicine and related indole alkaloids

Abstract: A compound, which accumulates when trypt-IN vivo feeding experiments with labelled potential preamine (I) and secologanin (11) are incubated with an cursors have led to the formulation of generally accepted enzyme preparation from Catharanthus roseus cell suspen-schemes for the biosynthesis of indole a1kaloids.l *2 The sion cultures, was identified as 20,2 1-didehydroaj malicine limitations of in vivo experiments were recently overcome (cathenamine) (IVa), and was shown to be a central when it was shown for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
1
25
0
2
Order By: Relevance
“…It has been demonstrated that strictosidine aglycon is converted to cathenamine via 4,21-dehydrocorynantheine aldehyde (18,20,31). In an analogous manner, it was found that the enamine 9 (Fig.…”
Section: ␤-D-glucosidase Of Ipecac Alkaloid Biosynthesismentioning
confidence: 67%
See 1 more Smart Citation
“…It has been demonstrated that strictosidine aglycon is converted to cathenamine via 4,21-dehydrocorynantheine aldehyde (18,20,31). In an analogous manner, it was found that the enamine 9 (Fig.…”
Section: ␤-D-glucosidase Of Ipecac Alkaloid Biosynthesismentioning
confidence: 67%
“…7), but the other one did not (data not shown). Accordingly, the formation of the ring-closed enamine 9 is the most probable, which is the counterpart to cathenamine that is formed by deglucosylation of strictosidine (20,31).…”
Section: Additive (Concentration)mentioning
confidence: 99%
“…[7,8] The ajmalicine pathway became the first example of an alkaloid biosynthetic pathway elucidated in detail through the participating enzymes. [9][10][11][12][13] Several suggestions had already been made at that time relating to the nature and participation of the first intermediate in indole alkaloid biosynthesis that was generated by condensation between the amine and the aldehyde secologanin. [14,15] The Catharanthus cell suspension cultures were optimized for efficient alkaloid production, [16,17] which turned out to be an excellent system to prove these suggestions.…”
Section: Detection Of the First Pictet-spenglerase And Structure Of Imentioning
confidence: 97%
“…A biomimetic approach was developed on the basis of the first known enzyme-catalyzed pathway leading to ajmalicine, [9][10][11][12] and is similar to a related chemoenzymatic route described earlier. [52,53] Starting with strictosidine, removal of the glucosyl group is the next reaction step catalyzed by strictosidine glucosidase (SG), obtained from crude or prepurified protein extracts of C. roseus or R. serpentina cell suspension cultures, or, if necessary, with the heterologously expressed 3D-structure-based modulated SG (Scheme 6).…”
Section: Str-based Biomimetic Approach To Heteroyohimbinesmentioning
confidence: 99%
“…After the work of Pictet and Spengler, the first asymmetric PSR was only performed in 1977, when an enzyme of the Pictet-Spenglerase class was discovered [4]. The enzyme-catalyzed PSR's has been recently reviewed [5].…”
Section: Introductionmentioning
confidence: 99%